Graphical data entry for SAPOR-s programming system - Gatalo, Ratko; Klarić, Rade; Hodolič, Janko (Journal of Production Engineering, 1990)
In this paper the newly developed module, called the ANG-Editor, for SAPOR-S system for automatic programming of NC machine tools for turning operations is presented. The ANG -Editor enables system-user communication at the level of Alpha-Numerical and Graphic information’s, which means, composing technological and geometric information’s about the product by step-by-step input of relevant data. In the first part of the paper the brief overview of the historical development of SAPOR-S system is given (from r. 1.0 to r.5.9). The second part brings the very SAPOR-S system. It describes feasibility and the already existing, day of data input by mean of SAPOR language. The third part deals with the basic concept for solving the very problem. It also presents the adopted model that was the base for the ANG-Editor's source code developing. The fourth part describes the ANG-Editor software package from the user's point of view. In the final, the fifth part of the paper, an example of generating the SAPOR language source code by mean of the ANG-Editor is described.